Work design, ICT use and service delivery of librarians in private universities in Oyo State, Nigeria - Ogungbade, Aderonke Ayobami; Oloyede, Oluwayemisi Eunice; Ozonuwe, Opene (Communicate: Journal of Library and Information Science, 2025)
The study investigated the influence of work design and ICT Use on the service delivery of librarians in private universities in Oyo State. A survey research design was adopted and data was collected from 374 undergraduates selected from a total population of 15,095 using simple random sampling. The method of data analysis used in the study is descriptive and inferential statistics, specifically simple linear regression and multiple linear regression at a 5% level of significance. Findings revealed that work design (Adj R2 = 0.177, F (1, 356) = 77.866, p < 0.05) and ICT Use (Adj. R2 = 0.055, F (1,356) = 21.839, p < 0.05) significantly influence service delivery of librarians in private university in Oyo state respectively and jointly (Adj R2 = 0.176, F (2, 356) = 39.121, p < 0.05). The study concludes that work design and ICT Use contribute to the quality service delivery of librarians in private universities in Oyo State. Recommendation includes the provision of ICT tools and the implementation of user feedback for quality service delivery.